Do Reputable Companies Produce a High Quality of Financial Statements? - Iman Harymawan; Dewi Nurillah (Emerald Publishing Limited, 2017)
The purpose of this study is to examine the relationship between corporate reputation and earnings quality. This study uses a sample of 1,092 firm year observations from 273 firm listed companies on the Indonesia Stock Exchange from 2013 to 2016, except for the financial industry. We uses a public measure, â€œ100 Top Emitenâ€ by Investor magazine, as a proxy for corporate reputation, while earnings quality is measured by calculating the absolute value of discretionary accrual. Growth of assets, firm size, leverage and profitability are used as control variables in this study. Multiple linear regression analysis is used to test the research hypothesis. The results of the regression in this study indicate that corporate reputation has a positive and significant relationship with earnings quality. This indicates that a reputable company will be encouraged to produce an earnings quality in an effort for the company to maintain investor confidence in the company, so that the company's image and reputation can be maintained. Earnings management in this study was calculated using cross-sectional method instead of time series method. Cross-sectional method is a method by comparing the financial data of a company with a company or other similar industries, whereas the time series method uses the comparison of financial data in a period with the previous period by analyzing what happens behind the trend figures on a company.